Targeting pathophysiological changes using biomaterials-based drug delivery systems: A key to managing inflammatory bowel disease - Mohajeri, Sahar; Moayedi, Saeed; Mohajeri, Shabnam; Yadegar, Abbas; Haririan, Ismaeil (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a gastrointestinal disorder, affecting about several million people worldwide. Current treatments fail to adequately control some clinical symptoms in IBD patients, which can adversely impact the patient’s quality of life. Hence, the development of new treatments for IBD is needed. Due to their unique properties such as biocompatibility and sustained release of a drug, biomaterials-based drug delivery systems can be regarded as promising candidates for IBD treatment. It is noteworthy that considering the pathophysiological changes occurred in the gastrointestinal tract of IBD patients, especially changes in pH, surface charge, the concentration of reactive oxygen species, and the expression of some biomolecules at the inflamed colon, can help in the rational design of biomaterials-based drug delivery systems for efficient management of IBD. Here, we discuss about targeting these pathophysiological changes using biomaterials-based drug delivery systems, which can provide important clues to establish a strategic roadmap for future studies.